Epstein–Barr virus DNA level as a novel prognostic factor in nasopharyngeal carcinoma: A meta-analysis. Issue 40 (October 2016) - Zhang, Jing; Shu, Chi; Song, Yanlin; Li, Qingfang; Huang, Jingwen; Ma, Xuelei
Abstract: Background: The plasma Epstein–Barr virus (EBV) DNA level in patients with nasopharyngeal carcinoma (NPC) performs as an appealing prognostic factor, but conclusions of its prognostic values from previous studies are inconsistent. In this study, we performed a comprehensive meta-analysis to evaluate the prognostic value of EBV DNA level in patients with NPC. Methods: Published studies were searched in PubMed. The baseline characteristics of patients, overall survival (OS), and other survival outcomes were extracted. Pooled hazard ratio (HR), 95% confidence interval (CI), and P value were calculated to estimate the prognostic value of EBV DNA level. Each cut-off value mentioned in the studies was obtained. Kaplan–Meier curves were used to extract data, and graphical survival plots were extracted for calculating HR when the study did not describe the information directly. Results: This meta-analysis pooled 23 eligible studies including 10, 732 patients with NPC. The pooled HR (95% CI) of pretreatment plasma EBV DNA level (pre-DNA) for OS was 2.78 (2.19, 3.55), and the HR (95% CI) of posttreatment plasma EBV DNA level (post-DNA) for OS was 5.43 (2.72, 10.82), suggesting that EBV DNA level was significantly correlated to the outcomes of patients with NPC. Conclusion: High expression levels of EBV DNA predicts poor prognosis in NPC.